Relationship between Myocardial Performance Index (Tei Index) and angiographic severity of coronary artery disease in patients with Acute ST Elevation Myocardial Infarction - Yadav, Sutap; Gajurel, Ratna Mani; Poudel, Chandra Mani; Khanal, Rajaram; Shah, Nischal; Ghimire, Roshan; Yadav, Lisha (Nepalese Heart Journal, 2024)
Background: Tei index is a Doppler derived measure of combined systolic and diastolic myocardial function and a better predictor of global LV function and outcome in patients with acute STEMI. The objective of this study was to determine the relationship between the myocardial performance index of LV (Tei index) and angiographic severity of coronary artery disease as assessed by SYNTAX score in patients with acute STEMI. Methods: This was a prospective, observational single centered study conducted from March 2022 to November 2022 at Manmohan Cardiothoracic Vascular and Transplant Centre, Institute of Medicine. (MCVTC, IOM). 160 patients with acute STEMI were enrolled. LV Tei index was calculated with the help of 2D and Tissue Doppler imaging, and the lesion severity was categorized with the help of SYNTAX score after the patients underwent coronary angiography. Results: The mean age was 61.23±12.33 years with a male preponderance. 107 (67%) were male with male to female ratio of 2:1. Tei index was significantly higher among the hypertensive (0.74±0.17) and diabetic (0.78±0.18) patients. 64 (40%), 51(31.9%) and 45(28.1%) had Single vessel disease (SVD), Double vessel disease (DVD) and Triple vessel disease (TVD) respectively with the Mean Tei index values 0.57 ± 0.10, 0.76 ± 0.11, and 0.88±0.11 (p<0.05). The Tei index increased when patients were divided into low, mid, and high SYNTAX score groups as 0.58±0.11, 0.61±0.73, 0.88±0.13 respectively, p-value < 0.05). Moreover, the study showed a positive correlation between Tei index and SYNTAX score with increasing severity of coronary artery stenosis. (r=0.654, p-value<0.001). Proximal LAD, LCx and RCA lesions had greater Tei index than the distal lesions. Conclusion: More proximally located LAD, LCx, RCA lesions had higher value of Tei index, as assessed with the SYNTAX score.